NY-ESO-1 protein glycosylated by yeast induces enhanced immune responses - Wadle, Andreas; Strahl, Sabine (Yeast, 2010)
Vaccine strategies that target dendritic cells to elicit potent cellular immunity are the subject of intense research. Here we report that the genetically engineered yeast Saccharomyces cerevisiae, expressing the full-length tumour-associated antigen NY-ESO-1, is a versatile host for protein production. Exposing dendritic cells (DCs) to soluble NY-ESO-1 protein linked to the yeast a-agglutinin 2 protein (Aga2p) protein resulted in protein uptake, processing and MHC class I cross-presentation of NY-ESO-1-derived peptides. The process of antigen uptake and cross-presentation was dependent on the glycosylation pattern of NY-ESO-1-Aga2p protein and the presence of accessible mannose receptors. In addition, NY-ESO-1-Aga2p protein uptake by dendritic cells resulted in recognition by HLA-DP4 NY-ESO-1-specific CD4+ T cells, indicating MHC class II presentation. Finally, vaccination of mice with yeast-derived NY-ESO-1-Aga2p protein led to an enhanced humoral and cellular immune response, when compared to the bacterially expressed NY-ESO-1 protein. Together, these data demonstrate that yeast-derived full-length NY-ESO-1-Aga2p protein is processed and presented efficiently by MHC class I and II complexes and warrants clinical trials to determine the potential value of S. cerevisiae as a host for cancer vaccine development. Copyright © 2010 John Wiley & Sons, Ltd.